Minority stress and selected mental disorders in people with gender dysphoria and gender incongruence - a narrative review - Magdalena Piegza; Patryk Główczyński (Nofer Institute of Occupational Medicine, 2022)
Gender incongruence according to the ICD-11, compiled by the World Health Organization in 2019, is a sense of inconsistency between experienced and assigned gender that does not have to be associated with discomfort or suffering. However, the aspect of suffering is emphasized in the understanding of the diagnostic unit of gender dysphoria according to the DSM-5 of the American Psychiatric Association. People with gender incongruence are exposed to misunderstanding, persecution and stigmatization, often related to experienced minority stress. The aim of this study was to analyze the available literature in terms of the relationship between gender dysphoria and some mental disorders and minority stress, and to draw attention to the suffering of these people in the context of social confrontation with the phenomenon of gender transposition. The unfavorable image of a person with gender dysphoria created by some media, persecution and, as a result, bans on gender reassignment in some countries mean that a steady increase in mental disorders in these patients can be expected. The main psychiatric problems in people with gender dysphoria, accompanied by minority stress for most of their lives so far, concern the coexistence of depressive and anxiety disorders, self-destructive behaviors and the tendency to addiction. An important aspect of the functioning of people with gender dysphoria are also difficulties in taking up and maintaining employment, fear of losing income due to attempting to live in accordance with the perceived gender. The authors of the presented review wanted to emphasize the importance of minority stress in the lives of these people and the need for social education and a change in the approach to the concept of "employee," excluding the record gender from it, which - according to the authors - could help people with gender incompatibility in their working life by reducing minority stress. Med Pr. 2022;73(2):163-72